PENGARUH STRATEGI PROMOSI, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA HOTEL BATAM VIEW BEACH RESORT - Dian Agustina Miranda; Mashur Fadli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the promotion strategy, service quality, and price of purchasing decisions at the Batam View Beach Resort Hotel. To determine the sample size using the Slovin formula with the sampling technique using the Accidental Sampling technique. For data collection techniques through questionnaires and literature studies, the types and sources of data used primary and secondary data. The measurement technique uses a Likert Scale. The results of the study confirm that there is a significant influence of promotion strategy, service quality, and price on purchasing decisions, but there are other variables that influence purchasing decisions. Keywords: Promotion Strategy, Service Quality, Price, Purchase Decision